Optimalisasi Partisipasi Masyarakat dalam Pengelolaan BUMDes Keramba Ikan di Desa Muaro Pijoan - Rahma Yani Putri, Reizzy Zickrullah Febrian, Fania Safitri, Adji Melandri, Chaya Nadinrly, Villa Oct (Integrative Perspectives of Social and Science Journal, 2026)
This study aims to analyze the optimization of village asset management in the form of fish cages through the Muaro Pijoan Jaya BUMDes and community participation in increasing Village Original Income (PAD) in Muaro Pijoan Village. This study uses the Collaborative Governance Regime (CGR) theory from Kirk Emerson, Tina Nabatchi, and Stephen Balogh with qualitative methods through observation and interviews with 7 informants, namely the Village Head, village secretary, hamlet head, RT 2 and RT 3 heads, and two community members. The results of the study indicate that transparent governance, clear division of roles, and active community participation. In addition, successful management is also influenced by compliance with regulatory frameworks such as Law Number 6 of 2014 concerning Villages. This study confirms that BUMDes-based village asset optimization not only increases village income but also strengthens community empowerment and economic independence through a participatory approach and sustainable management.